2019
DOI: 10.3390/ijerph16183303
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Release Potential of Sediments in Reservoirs and its Impact on Water Quality Assessment

Abstract: Reservoir sediments act as important receivers and sources for nutrients in the overlaying water. To determine the sediments adsorption and release characteristics and their impacts on water quality, surface sediments samples collected from Biliuhe reservoir in August 2015 were studied through simulation experiments in a laboratory. The results demonstrated that the equilibrium concentrations (EC0) of ammonia nitrogen (NH4+–N) and total phosphorus (TP) were 8.29 mg/L and 0.025 mg/L, respectively, which were bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 45 publications
4
7
0
Order By: Relevance
“…This is in line with the research by Wiatkowski and Czerniawska-Kusza (2009) 73 and Gruss et al (2021) 43 , who indicated that the water analyzed in the Turawa reservoir in spring and summer, as a result of rising temperatures and increased pH, was characterized by the release of phosphorus from deeper sediment layers to the surface water. This tendency was also confirmed by the research of Hu et al (2019) 74 on the Biliuhe reservoir in China and Moura et al (2020) 75 on three water bodies in Brazil.…”
Section: Discussionsupporting
confidence: 66%
“…This is in line with the research by Wiatkowski and Czerniawska-Kusza (2009) 73 and Gruss et al (2021) 43 , who indicated that the water analyzed in the Turawa reservoir in spring and summer, as a result of rising temperatures and increased pH, was characterized by the release of phosphorus from deeper sediment layers to the surface water. This tendency was also confirmed by the research of Hu et al (2019) 74 on the Biliuhe reservoir in China and Moura et al (2020) 75 on three water bodies in Brazil.…”
Section: Discussionsupporting
confidence: 66%
“…It is generally believed that hydrolysis enzymes break down nitrogen-containing organic compounds into low molecular weight components, such as amino acids, peptides, and nucleic acids, in the process of ammoniation taking place in the water-sediment interface [22,23]. These low molecular weight substances are quickly degraded by bacteria in the water and sediments, together with the release of organic acids and ammonia.…”
Section: Effect Of Thermal Stratification On Dissolved Oxygen and Amm...mentioning
confidence: 99%
“…In adverse thermal and oxygen conditions the presence of sediments contributed to secondary contamination of the stored rainwater -e.g. an increase in turbidity due to resuspension or release of phosphorus in biochemical processes (Hu et al 2019). Analyses of certain chemical and biochemical properties of sediments carried out in 2007 showed significant concentrations of organic carbon (on average 4,540.00 mg•kg -1 ) and NH 4 + (on average 83.05 mg•kg -1 ) in the settler (Zubala et al 2007).…”
Section: Tablementioning
confidence: 99%